2016
DOI: 10.1038/srep38316
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Conversion of Lipophilic Substrates by Phase constrained Enzymes in the Aqueous or in the Membrane Phase

Abstract: Both soluble and membrane-bound enzymes can catalyze the conversion of lipophilic substrates. The precise substrate access path, with regard to phase, has however, until now relied on conjecture from enzyme structural data only (certainly giving credible and valuable hypotheses). Alternative methods have been missing. To obtain the first experimental evidence directly determining the access paths (of lipophilic substrates) to phase constrained enzymes we here describe the application of a BODIPY-derived substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…MGST1 is an integral membrane enzyme facing the challenge of conjugating a hydrophilic substrate (GSH) with a hydrophobic electrophile entering the enzyme from the membrane phase (Figure 8) 15 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MGST1 is an integral membrane enzyme facing the challenge of conjugating a hydrophilic substrate (GSH) with a hydrophobic electrophile entering the enzyme from the membrane phase (Figure 8) 15 .…”
Section: Resultsmentioning
confidence: 99%
“…MGST1 is an integral membrane enzyme facing the challenge of conjugating a hydrophilic substrate (GSH) with a hydrophobic electrophile entering the enzyme from the membrane phase (Figure 8). 15 A cleft between subunits opens to the membrane phase, allowing hydrophobic substrate access. 11 The cleft is covered by a loop that must open and close over GSH entering from the cytosol.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the stereochemistry of product formation in cells it could be demonstrated that conjugation is predominantly catalyzed by MGST1, even though the GST catalytic capacity of isolated cytosolic and membrane fractions were equal in vitro. In general, cytosolic GSTs cannot access membrane-embedded substrates [ 89 ], and act upon the fraction that equilibrates out from the membrane phase (governed by logP [ 71 ]). Membrane-bound MGST1, conversely, cannot access the cytosolic substrate fraction [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since TRAST does not rely on fluctuation measurements of single molecules, molecular brightness is not a strongly limiting issue, and low fluorescence signals can be compensated by higher concentrations of fluorescent molecules in the sample, as an alternative to increased excitation irradiances. Thereby, also relatively low brightness compounds, such as autofluorescent species (Hevekerl et al 2016 ), can be studied.…”
Section: Transient-state (Trast) Spectroscopy/imaging To Exploit the mentioning
confidence: 99%